A construction method for conformal mapping of the unit disk onto a Riemann surface - P.N. Ivanshin (Учёные записки Казанского университета: Серия Физико-математические науки)
A construction method for approximate conformal mapping of the unit disk onto a Riemann surface (a map with a self-overlapping image) has been described. An example has been provided to illustrate the applicability of the method to conformal mapping of the unit disk onto a two-sheeted covering of the domain by a Riemann surface.